Recognizing plague epidemics in the archaeological record of West Africa - Daphne E. Gallagher; Stephen A. Dueppen (Afriques)
Many archaeological sites in the central West African savanna were either abandoned or reduced in size between the 14th and 15th centuries CE. Explanations have tended to invoke the effects of climate change (increasing aridity), political transformations, and religious conversion. However, more recently scholars have increasingly suggested that this regional pattern could be in part the result of plague epidemics. In this paper we explore the methodological challenges inherent in linking abandonments with the effects of epidemics in the archaeological record through a contextualized examination of settlement pattern data from recent archaeological research at sites in Burkina Faso and Mali. While plague cannot be definitively identified based on settlement pattern data alone, current evidence supports the possibility that plague affected populations in this area of West Africa. A broader view of sites throughout West Africa indicates that the possible effects of plague were widespread.